Effects of Bacillus subtilis PB6 (CLOSTAT 500) Incorporation Into a Commercial Mineral Supplement on Growth Performance and Health of Beef Stocker Calves Grazing in the Kansas Flint Hills - Z. M. Duncan; W. Cole Ellis; Macie C. Weigand; Colton D. Weir; William R. Hollenbeck; J. T. Leonhard; S. J. Trojan; J. E. Hergenreder; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this experiment was to determine if incorporating Bacillus subtilis PB6 (CLOSTAT; Kemin Industries, Inc.) into a commercial mineral supplement would improve the growth performance and health of beef stocker calves grazing in the Kansas Flint Hills. Study Description: During the summer of 2024, 495 crossbred beef steers were randomly assigned to one of 18 pastures. Pastures were randomly assigned to receive one of two mineral supplements: a commercial mineral supplement (Control) or a commercial mineral supplement that contained 0.5 g/head/d CLOSTAT 500 (CLOSTAT; Kemin Industries, Inc., Des Moines, IA). Steers were grazed for 90 days from May to August, and mineral supplements were delivered twice weekly to provide 4 oz/head/day. Individual body weights were measured at the beginning and end of the grazing period. The Bottom Line: Feeding a commercial mineral supplement that contained Bacillus subtilis PB6 (CLOSTAT 500) did not improve growth performance, pinkeye prevalence, or health of crossbred beef steers grazing in the Kansas Flint Hills.
Keywords: Bacillus subtilis PB6; CLOSTAT; stocker cattle